Flame-retardant wrapping belt based on wide-range biomass fiber and preparation process thereof

CN120645409BActive Publication Date: 2026-10-23QINGDAO HANHE CABLE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510723613.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-31
Publication Date
2026-10-23
Estimated Expiration
2045-05-31

AI Technical Summary

Benefits of technology

[0027]本发明提供的基于宽域生物质纤维的阻燃绕包带及其制备工艺,打破材料限制,组分中采用的生物质纤维、无机阻燃剂和辅助功能剂等材料宽域兼容,可选种类较多;并对制备工艺进行创新,采用动态负压浸渍(DVI),在-0.05~-0.1MPa负压下实现纤维孔隙的矿物纳米渗透;采用高剪切狭缝挤出取向(USCO),在高剪切速率(1200~2000s-1)下,通过狭缝挤出模具,定向排列片晶,实现取向度>85%;采用柔性相变干燥(FPD),通过石蜡微球相变(熔点60~80℃)实现非破坏性收缩定型。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005429985610000041
    Figure BDA0005429985610000041
  • Figure BDA0005429985610000051
    Figure BDA0005429985610000051
Patent Text Reader

Abstract

The application belongs to the field of cable flame-retardant material manufacturing, and relates to a wide-range biomass fiber-based flame-retardant wrapping tape and a preparation process thereof. An inorganic flame retardant and an auxiliary functional agent are dispersed in water, stirred after pH adjustment to form an aqueous slurry, mixed with biomass fibers, and subjected to negative pressure ultrasonic oscillation; acid is continuously added until pH is 4.8-5.3, and the mixture is left to stand for 15-30 min; acid is slowly added until pH is 4.0-4.5, and the mixture is slowly stirred until a semi-finished product gel is formed; the semi-finished product gel is conveyed to a slit die, set at 55-65 DEG C, 1-1.5 MPa, and extruded for 1200-2000 s ‑1 to form a sheet-shaped tape; the surface of the tape is sprayed with paraffin microspheres, heated at 65-75 DEG C for 2-3 min, and gradually cooled through a temperature gradient to complete solidification molding. The wide-range adaptive flame-retardant wrapping tape is prepared by adopting a dynamic negative pressure impregnation-slit extrusion orientation process, has strong material compatibility, realizes universal production, and has a wide application scenario.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of cable flame retardant material manufacturing, specifically relating to a flame retardant wrapping tape based on wide-range biomass fibers and its preparation process. Background Technology

[0002] Wrapping tape is an auxiliary material widely used in cables, wires, and other fields to wrap cable conductors and cable cores. Its main functions are twofold: first, to wrap and braid conductors, preventing the conductor bundles from loosening and smoothing the conductor surface to facilitate the extrusion of the conductor shielding layer; second, to wrap around the insulation shielding layer of the cable core, protecting the internal cable core and acting as a buffer and pad during the thermal expansion of the cable core. It also provides certain functions such as heat insulation, corrosion protection, and flame retardancy.

[0003] Traditional methods for preparing wrapping tape mainly use materials such as nylon, non-woven fabric, and glass fiber, and add various functional additives to improve its performance. However, these methods are environmentally unfriendly, and due to the aforementioned matrix structure, ablation occurs during cable operation. This solution uses environmentally friendly fibers as the base material and acid source, making it environmentally friendly, and the resulting product has higher resistance to ablation. Summary of the Invention

[0004] The purpose of this invention is to solve the above-mentioned problems existing in the prior art, and to propose a flame-retardant wrapping tape based on wide-range biomass fiber and its preparation process. The wide-range adaptable flame-retardant wrapping tape is prepared by dynamic negative pressure impregnation-slit extrusion orientation process. On the material side, it is compatible with multi-element biomass fiber and inorganic mineral flame-retardant system. On the process side, it achieves high-performance universal production through gradient acidification, shear fluid field control and flexible phase change drying. It is suitable for a wide range of applications from low-voltage home decoration cables to ultra-high voltage DC cables.

[0005] The technical solution of this invention is:

[0006] This invention provides a process for preparing flame-retardant wrapping tape based on wide-range biomass fibers, comprising the following steps:

[0007] (1) According to the composition of flame-retardant wrapping tape, inorganic flame retardant and auxiliary functional agent are dispersed in deionized water, and the solid content is controlled to be 25% to 30%. Then, an acid source is added to adjust the pH to 5.5 to 6.0, and the mixture is stirred at high speed to form an aqueous slurry. The aqueous slurry is mixed with biomass fiber and ultrasonically vibrated under a negative pressure of -0.05MPa to -0.1MPa.

[0008] (2) Continue to add acid source to adjust the pH value to 4.8-5.3, let stand for 15-30 minutes to allow the fiber to swell; then slowly add acid source to the pH value to 4.0-4.5, stir at low speed until cross-linking forms a semi-finished gel;

[0009] (3) The semi-finished gel is conveyed to the slit mold, and the temperature is controlled at 55-65℃, which can maintain the thermoplasticity of the gel; the pressure is controlled at 1-1.5MPa through feedback adjustment of the pressure sensor, and the linear speed is set to 20-25m / min (corresponding to a shear rate of 1200-2000s). -1 ), in the 1200-2000s -1 Sheet material is extruded under shear rate to form sheet or strip material;

[0010] (4) Spray paraffin microspheres onto the surface of the extruded tape, heat at 65-75℃ for 2-3 minutes, and then gradually cool through a set temperature gradient to complete the curing and molding process, thus obtaining the flame-retardant wrapping tape product.

[0011] Furthermore, the flame-retardant wrapping tape comprises the following components by mass percentage: 50-60% biomass fiber, 25-35% inorganic flame retardant, and 5-15% auxiliary functional agent;

[0012] The biomass fiber includes one or more of α-cellulose, bamboo pulp fiber, or straw fiber; the biomass fiber is used to provide a mechanical framework.

[0013] The inorganic flame retardant includes any one or more of hydrotalcite, magnesium hydroxide, aluminum hydroxide, zinc borate, phosphogypsum, ammonium polyphosphate, or aluminum hypophosphite; the inorganic flame retardant can synergistically retard flames and has a decomposition temperature of 200–600°C.

[0014] The auxiliary functional agent includes any one or more of expanded graphite, nano-clay, carbon nanotubes or silicon carbide; the auxiliary functional agent plays a role in enhancing thermal conductivity / insulation.

[0015] Furthermore, the acid source includes any one or more of citric acid, phytic acid, or ammonium dihydrogen phosphate.

[0016] Furthermore, in step (1), the high-speed stirring speed is 80-100 rad / min.

[0017] Furthermore, in step (1), the biomass fiber is pre-opened, mixed with the aqueous slurry, and then subjected to negative pressure and ultrasonic oscillation at 20kHz to 30kHz for 5 to 10 minutes, so that the particles in the aqueous slurry impregnate and penetrate into the fiber pores.

[0018] Furthermore, in step (2), the speed of the low-speed stirring is 10 to 15 rad / min.

[0019] Furthermore, the parameters of the slit mold used in step (3) are as follows:

[0020] The seam width (W) is 0.3–0.8 mm, and the extrusion thickness is controlled (final strip thickness 0.5–1.2 mm).

[0021] The slit length (L) is 300–500 mm, which affects the shearing time (dwell time 0.1–0.5 s).

[0022] The inlet expansion angle is 30° to 60° to optimize flow uniformity;

[0023] Surface roughness (Ra) ≤ 0.1 μm, reducing flow channel adhesion.

[0024] Furthermore, in step (4), paraffin microspheres with a particle size of 5-20 μm are sprayed onto the surface of the strip, and phase change penetration is triggered by infrared heating at 65-75℃. Then, the temperature gradient is set at 43-47℃ for slow cooling and shaping for 5-8 minutes, and 23-27℃ for final cooling and stabilization for 3-5 minutes. The strip is gradually cooled to reduce the shaping shrinkage rate of the material.

[0025] The present invention also provides a flame-retardant wrapping tape based on wide-range biomass fibers, wherein the flame-retardant wrapping tape is prepared by any of the above-described preparation methods.

[0026] The beneficial effects of this invention are:

[0027] This invention provides a flame-retardant wrapping tape based on broad-domain biomass fibers and its preparation process. It overcomes material limitations, allowing for broad compatibility of biomass fibers, inorganic flame retardants, and auxiliary functional agents in its components, offering a wide range of choices. Furthermore, it innovates the preparation process by employing dynamic negative pressure impregnation (DVI) to achieve mineral nano-permeation of the fiber pores under a negative pressure of -0.05 to -0.1 MPa; and by using high-shear slotted extrusion orientation (USCO) at high shear rates (1200–2000 s⁻¹). -1 Under the conditions of ) through a slit extrusion die, the crystal sheets are oriented to achieve an orientation degree of >85%; flexible phase change drying (FPD) is used to achieve non-destructive shrinkage and shaping through the phase change of paraffin microspheres (melting point 60-80℃). Detailed Implementation

[0028] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0029] This invention provides a process for preparing flame-retardant wrapping tape based on wide-range biomass fibers, comprising the following steps:

[0030] (1) Dynamic negative pressure impregnation premix

[0031] Prepare the raw materials for flame-retardant wrapping tape according to the following mass percentages:

[0032] 50-60% biomass fiber (any one or more of α-cellulose, bamboo pulp fiber or straw fiber), 25-35% inorganic flame retardant (any one or more of hydrotalcite, magnesium hydroxide, aluminum hydroxide, zinc borate, phosphogypsum, ammonium polyphosphate or aluminum hypophosphite) and 5-15% auxiliary functional agent (any one or more of expanded graphite, nano clay, carbon nanotubes or silicon carbide).

[0033] Inorganic flame retardants and auxiliary functional agents are dispersed in deionized water, with the solid content controlled at 25% to 30%. An appropriate amount of acid source is added to adjust the pH to 5.5 to 6.0. The mixture is stirred at high speed at 80 to 100 rad / min to form an aqueous slurry.

[0034] After pre-opening the biomass fibers, they are loaded into a sealed reactor, and an aqueous slurry containing inorganic flame retardants and auxiliary functional agents is injected and mixed. A negative pressure of -0.05MPa to -0.1MPa is applied, and ultrasonic vibration at 20kHz to 30kHz is applied for 5 to 10 minutes to allow the additive particles to penetrate into the fiber pores.

[0035] (2) Gradient acidification gelation

[0036] Continue adding acid to adjust the pH value:

[0037] Primary swelling: Continue adding acid source until pH = 4.8-5.3, and let stand for 15-30 minutes to allow the fiber to swell;

[0038] Deep cross-linking: Continue to slowly add acid until the pH is 4.0 to 4.5, while stirring at a low speed of 10 to 15 rad / min until a semi-finished gel is formed.

[0039] (3) Variable cross-section flow channel slit extrusion

[0040] The semi-finished gel is conveyed to a slot die via a single-screw extruder, with the temperature controlled at 55–65°C and the pressure at 1–1.5 MPa, and the extrusion time at 1200–2000 s. -1 Sheet material is extruded under shear rate to form sheet or strip material;

[0041] The slit parameters are as follows: slit width 0.3–0.8 mm, slit length 300–500 mm, inlet expansion angle 30°–60°, and surface roughness ≤0.1 μm.

[0042] (4) Flexible phase change drying

[0043] Paraffin microspheres with a particle size of 5–20 μm and a melting point of about 70 °C are sprayed onto the surface of the extruded strip. The strip is then heated with infrared heat at 65–75 °C for 2–3 min to trigger phase change penetration, which fills the pores and sets the shape. The strip is then passed through a modular temperature-controlled tunnel furnace for gradual cooling to reduce the shaping shrinkage rate of the material.

[0044] The temperature gradient settings in step (4) above are shown in Table 1:

[0045] Table 1 shows the set temperature gradient.

[0046] Melt penetration zone 70±5 2~3 Paraffin melts and penetrates into the pores of the strip. Slow cooling and shaping zone 45±2 5~8 Paraffin partially crystallizes, inhibiting strip shrinkage. Final cooling stability region 25±2 3~5 Complete curing and molding

[0047] By gradually cooling the product using a set temperature gradient, solidification and molding are completed, ultimately producing a flame-retardant wrapping tape product.

[0048] Example 1

[0049] Straw fiber-based flame-retardant tape

[0050] Formula: 60% straw fiber, 20% phosphogypsum, 10% hydrotalcite, and 10% expanded graphite.

[0051] Its preparation process includes the following steps:

[0052] (1) According to the formula composition, phosphogypsum, hydrotalcite and expanded graphite are dispersed in deionized water, the solid content is controlled at 30%, an appropriate amount of 8% ammonium dihydrogen phosphate is added to adjust the pH to 5.3, and the mixture is stirred at 90 rad / min to form an aqueous slurry.

[0053] After pre-opening the straw fibers, they were loaded into a sealed reaction vessel, and water-based slurry was injected and mixed. A negative pressure of -0.1MPa was applied, and ultrasonic vibration at 25kHz was performed for 7 minutes.

[0054] (2) Continue adding ammonium dihydrogen phosphate until pH = 5.0, let stand for 25 min to allow the fiber to swell; then continue to slowly add ammonium dihydrogen phosphate until pH = 4.2, while stirring slowly at 12 rad / min until a semi-finished gel is formed;

[0055] (3) The semi-finished gel is fed into a slit die (slit width 0.5 mm, slit length 400 mm, inlet expansion angle 50°, surface roughness 0.1 μm) through a single screw extruder, and the temperature is controlled at 60℃ and the pressure at 1.2 MPa, and the extrusion time is 1600 s. -1 Sheet material is extruded under shear rate to form sheet or strip material;

[0056] (4) Spray paraffin microspheres with a particle size of 10 μm and a melting point of about 70 °C onto the surface of the extruded strip. Trigger phase change penetration by infrared heating at 70 °C for 2.5 min, then slowly cool and shape at 45 °C for 6 min, and finally cool and stabilize at 25 °C for 4 min. Gradually cool the strip to complete the curing and shaping, and finally prepare the straw fiber-based flame-retardant wrapping tape.

[0057] The performance of the prepared straw fiber-based flame-retardant wrapping tape was tested, and the test results are shown in Table 2 below.

[0058] Table 2 Performance test data of straw fiber-based flame-retardant wrapping tape

[0059]

[0060]

[0061] Example 2

[0062] High-strength α-cellulose-based cable tape

[0063] Formula: α-cellulose 58%, zinc borate 23%, nano clay 9%, silicon carbide 10%.

[0064] Its preparation process includes the following steps:

[0065] (1) According to the formula composition, zinc borate, nano clay and silicon carbide are dispersed in deionized water, the solid content is controlled at 25%, and an appropriate amount of phytic acid with a concentration of 8% is added to adjust the pH to 5.5. The mixture is stirred at a speed of 80 rad / min to form an aqueous slurry.

[0066] After pre-opening α-cellulose, it was loaded into a closed reactor, and an aqueous slurry was injected and mixed. A negative pressure of -0.05MPa was applied, and ultrasonic oscillation at 20kHz was performed for 5 minutes.

[0067] (2) Continue adding phytic acid until pH = 4.8, let stand for 15 min to allow the fiber to swell; then continue to slowly add phytic acid until pH = 4.0, while stirring slowly at 10 rad / min until a semi-finished gel is formed;

[0068] (3) The semi-finished gel is fed into a slit die (slit width 0.3 mm, slit length 300 mm, inlet expansion angle 30°, surface roughness ≤0.1 μm) through a single screw extruder, and the temperature is controlled at 55℃ and the pressure at 1 MPa for 1400 s. -1 Sheet material is extruded under shear rate to form sheet or strip material;

[0069] (4) Spray paraffin microspheres with a particle size of 5μm and a melting point of about 70℃ onto the surface of the extruded tape. Infrared heating at 65℃ for 2min triggers phase change penetration. Then, slow cooling at 43℃ for 5min and final cooling at 23℃ for 3min stabilizes the tape. The tape is gradually cooled to complete the curing and molding process, and finally a high-strength α-cellulose-based flame-retardant wrapping tape is prepared.

[0070] The performance of the prepared high-strength α-cellulose-based flame-retardant wrapping tape was tested, and the test results are shown in Table 3 below.

[0071] Table 3. Performance test data of high-strength α-cellulose-based flame-retardant wrapping tape

[0072] Limiting oxygen index (LO%) 53 42 GB5454 Tensile strength (N / 2.5cm) 240 180 ISO9073.3 Thermal conductivity (W / mK) 0.1 0.3 ASTM E1461 <![CDATA[Peak heat release rate (kW / m 2 )]]> 35(600℃) 120(500℃) ISO5660-1

[0073] Example 3

[0074] Bamboo pulp-based high-flexibility flame-retardant tape

[0075] Formula: 50% bamboo pulp fiber, 35% aluminum hydroxide, 10% expanded graphite, and 5% carbon nanotubes.

[0076] Its preparation process includes the following steps:

[0077] (1) According to the formula composition, aluminum hydroxide, expanded graphite and carbon nanotubes are dispersed in deionized water, the solid content is controlled at 30%, an appropriate amount of 10% citric acid is added to adjust the pH to 6.0, and the mixture is stirred at 100 rad / min to form an aqueous slurry.

[0078] After pre-opening the bamboo pulp fiber, it was loaded into a closed reaction vessel, water-based slurry was injected and mixed, a negative pressure of -0.1MPa was applied, and ultrasonic oscillation at 30kHz was performed for 10 minutes.

[0079] (2) Continue adding citric acid until pH = 5.3, let stand for 30 min to allow the fiber to swell; then continue to slowly add citric acid until pH = 4.5, while stirring slowly at 15 rad / min until a semi-finished gel is formed;

[0080] (3) The semi-finished gel is fed into a slit die (slit width 0.8 mm, slit length 500 mm, inlet expansion angle 60°, surface roughness ≤0.1 μm) through a single screw extruder, and the temperature is controlled at 65℃ and the pressure at 1.5 MPa for 1200 s. -1 Sheet material is extruded under shear rate to form sheet or strip material;

[0081] (4) Spray paraffin microspheres with a particle size of 20μm and a melting point of about 70℃ onto the surface of the extruded tape. Infrared heating at 75℃ for 3min triggers phase change penetration. Then, slow cooling at 47℃ for 8min and final cooling at 27℃ for 5min stabilizes the tape. The tape is gradually cooled to complete the curing and molding process, and finally bamboo pulp-based high flexibility flame retardant wrapping tape is prepared.

[0082] The performance of the prepared bamboo pulp-based high-flexibility flame-retardant wrapping tape was tested, and the test results are shown in Table 4 below.

[0083] Table 4 Performance test data results of bamboo pulp-based high-flexibility flame-retardant wrapping tape

[0084] Limiting oxygen index (LO%) 50 42 GB5454 Tensile strength (N / 2.5cm) 270 180 ISO9073.3 Elongation at break (%) 43 14 ISO9073.3 Thermal conductivity (W / mK) 0.1 0.3 ASTM E1461 <![CDATA[Peak heat release rate (kW / m 2 )]]> 43(600℃) 120(500℃) ISO5660-1

[0085] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, alterations, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A preparation process for flame-retardant wrapping tape based on wide-range biomass fibers, characterized in that, Includes the following steps: (1) According to the composition of flame-retardant wrapping tape, inorganic flame retardant and auxiliary functional agent are dispersed in deionized water, and the solid content is controlled to be 25%~30%. Then, an acid source is added to adjust the pH to 5.5~6.0, and the mixture is stirred at high speed to form an aqueous slurry. The aqueous slurry is mixed with biomass fiber and ultrasonically vibrated under a negative pressure of -0.05 MPa~ -0.1 MPa. (2) Continue to add acid source to adjust the pH value to 4.8~5.3, let stand for 15~30 min to allow the fiber to swell; then slowly add acid source to the pH value to 4.0~4.5, stir at low speed until cross-linking forms a semi-finished gel; (3) The semi-finished gel is conveyed to the slit mold, and the temperature is controlled at 55~65℃, the pressure at 1~1.5 MPa, and the pressure is controlled at 1200~2000 s. -1 Sheet material is extruded under shear rate to form sheet or strip material; (4) Spray paraffin microspheres onto the surface of the extruded tape, heat at 65~75℃ for 2~3 min, and then gradually cool through the set temperature gradient to complete the curing and molding process, thereby obtaining the flame-retardant wrapping tape product. The flame-retardant wrapping tape comprises the following components by mass percentage: 50-60% biomass fiber, 25-35% inorganic flame retardant, and 5-15% auxiliary functional agent; The biomass fiber includes any one or more of α-cellulose, bamboo pulp fiber, or straw fiber; The inorganic flame retardant includes any one or more of hydrotalcite, magnesium hydroxide, aluminum hydroxide, zinc borate, phosphogypsum, ammonium polyphosphate, or aluminum hypophosphite. The auxiliary functional agent includes any one or more of expanded graphite, nano-clay, carbon nanotubes, or silicon carbide.

2. The preparation process according to claim 1, characterized in that, The acid source includes any one or more of citric acid, phytic acid, or ammonium dihydrogen phosphate.

3. The preparation process according to claim 1, characterized in that, In step (1), the speed of high-speed stirring is 80~100 rad / min.

4. The preparation process according to claim 1, characterized in that, In step (1), the biomass fiber is pre-opened, mixed with the aqueous slurry, and then subjected to negative pressure and ultrasonic oscillation at 20 kHz to 30 kHz for 5 to 10 minutes, so that the particles in the aqueous slurry impregnate and penetrate into the fiber pores.

5. The preparation process according to claim 1, characterized in that, In step (2), the speed of low-speed stirring is 10~15 rad / min.

6. The preparation process according to claim 1, characterized in that, The slit mold used in step (3) has a slit width of 0.3~0.8 mm, a slit length of 300~500 mm, an inlet expansion angle of 30°~60°, and a surface roughness of ≤0.1 μm.

7. The preparation process according to claim 1, characterized in that, In step (4), paraffin microspheres with a particle size of 5~20 μm are sprayed onto the surface of the strip. Phase change penetration is triggered by infrared heating at 65~75℃. Then, the temperature gradient is set at 43~47℃ for slow cooling and shaping for 5~8 min, and 23~27℃ for final cooling and stabilization for 3~5 min. The strip is gradually cooled to reduce the shaping shrinkage rate of the material.

8. A flame-retardant wrapping tape based on wide-range biomass fibers, characterized in that, The flame-retardant wrapping tape is prepared using the manufacturing process described in any one of claims 1-7.

Citation Information

Patent Citations

  • Warping tape applied to corrosion prevention and insulation of special cables and preparation method thereof

    CN107841827A

  • Flame-retardant regenerated cellulose fiber and preparation method thereof

    CN110067034A

  • PP wrapping tape for wire and cable production and manufacturing method thereof

    CN114163727A